META-IMAGE – A COLLABORATIVE ENVIRONMENT FOR IMAGE DISCOURSE - Dieckmann, Lisa; Kliemann, Anita; Warnke, Martin (International Journal of Computing, 2010)
The aim of the project Meta-Image, funded by German Research Foundation (DFG), is to provide a networkbased research environment for art history and other sciences concerning visual culture. It consists of the two components prometheus and HyperImage. Meta-Image combines the distributed digital image archive prometheus, which consists of a very large pool of images, with HyperImage (http://www.hyperimage.eu), a tool for image annotation. prometheus provides over 700,000 images in nearly 60 connected image databases; Hyperimage facilitates collaborative work directly on the image. The numerous users, the secure legal context for use and the existing technologies for collaborative research make prometheus a perfect subject for HyperImage. This image annotation tool serves as an instrument to support research in art history. It allows the identification of motifs, the creation of linked image networks as well as the addition of metadata. This synthesis creates the ability to reorganise, juxtapose and annotate images in a way that can lead to new conclusions concerning image-based research. Art history and other cultural studies can finally realise the potential of the network based and collaborative analysis of images.